The Impact of Rotational Malalignment Following Intramedullary Nailing for Intertrochanteric Fractures on Patients’ Functional Outcomes: A Prospective Study - Michail Vavourakis; Athanasios Galanis; Dimitrios Zachariou; Evangelos Sakellariou; Christos Patilas; Panagiotis Karampinas; Angelos Kaspiris; Meletis Rozis; John Vlamis; Elias Vasiliadis; Spiros Pneumaticos (Journal of Functional Morphology and Kinesiology)
Background & Aims: Rotational malalignment after intramedullary nailing of intertrochanteric fractures is a relatively common complication that may have a crucial impact on both functional outcome and a fracture’s healing properties, ultimately affecting the patient’s postoperative morbidity and mortality. Methods: 74 patients treated with intramedullary nailing due to an intertrochanteric fracture underwent a postoperative computed tomography (CT) scan of the hips and knees. The femoral anteversion difference (D angle) between the operated and healthy hip was calculated using the technique described by Jeanmart’s method. The patients were divided into two groups according to their D angle values: a D angle less than 15° was considered an acceptable rotational alignment (group A), while a D angle equal to or more than 15° was considered a rotational deformity (group B). Postoperatively, the functional level of each patient was evaluated at the 6-month and 1-year follow-up visits and compared to the pre-fracture status using the modified Harris hip score (mHHS). Also, fracture union, other postoperative complications, and patient mortality were noted. Results: The mean femoral anteversion difference was 12.3° with a standard deviation of 10.3°. Of the 74 patients, 51 (68.9%) were assigned to group A and 23 (31.1%) to group B. At the 6-month postoperative follow-up, 67 (90.5%) patients had survived and 7 (9.5%) were deceased, with our statistical analysis indicating a linear trend (p-value = 0.048) between the presence of rotational malalignment and 6-month mortality. At the 1-year postoperative follow-up, 63 (85.1%) patients survived and 11 (14.9%) were deceased, with the statistical analysis indicating a significant relationship (p-value = 0.031) between the presence of rotational malalignment and the 1-year mortality. Regarding the functional outcome six months after the operation, the difference between the pre-fracture and the postoperative mHHS was 8.7/100 with a standard deviation of 6.1 for the 49 patients in group A and 14.5/100 with a standard deviation of 12.4 for the 18 patients in group B, with the statistical analysis indicating a significant difference (t = −2.536, significance < 0.05) in the functional level between the two groups. As for the functional outcome one year after the operation, the difference between the pre-fracture and the postoperative mHHS was 4.9/100 with a standard deviation of 7.8 for the 47 patients in group A and 8.3/100 with a standard deviation of 13 for the 16 patients in group B, with the statistical analysis indicating no significant difference (t = −1.266, significance > 0.05) in the functional level between the two groups. The only postoperative complication noted was fracture non-union, presenting in two patients (3%), with the statistical analysis indicating no significant relationship (p-value = 0.698) between this complication and the presence of rotational malalignment. Conclusions: In this study, rotational malalignment after intertrochanteric fracture intramedullary nailing presents in 31.1% of cases. The correlation between this malalignment and functional outcomes shows a decline in patients’ functional abilities during the first six postoperative months, a condition that improves over time, with most patients returning to their preoperative functional status one year after the operation. Furthermore, our results indicate a possible relationship between rotational malalignment and mortality within one year. Future research should focus on creating a more detailed, functional evaluation system for the elderly and applying it to a larger sample to confirm these findings.